The Effect Of Individual Morality, Good Corporate Governance On Accounting Fraud With Moderation Of Organizational Culture - Oktavianingsih, Rahma; Satya Pradhana, Wira (Journal of Accounting and Finance, 2025)
Purpose – This study aims to examine how Individual Morality and Good Corporate Governance affect accounting fraud and assess how Organizational Culture moderate Individual Morality and Good Corporate Governance on Accounting Fraud.Design/methodology/approach – This research uses quantitative methods, with primary data collected from a population of 120 people who work in the Shopee Marketplace. Data analysis was carried out using smartPLS software with Moderated Regression AnalysisFindings – Individual Morality has a negative and statistically insignificant effect on Accounting Fraud, Good Corporate Governance has a positive and statistically significant effect on Accounting Fraud, Organizational Culture can strengthen the relationship between Individual Morality on Accounting Fraud, Organizational Culture cannot strengthen the relationship between Good Corporate Governance and Accounting Fraud.Originality/value – This research focuses on Accounting Fraud, where this research is a new research in discussing the relationship between Individual Morality and Good Corporate Governance in the Shopee marketplace.